Copyright Protection for The Works of Sae Lecturers and Students in The Creative Media Field in The Instant Gratification Era - RR. Ella Evrita H (Publikasi Indonesia, 2021)
The protection of ideas or creativity on the work, especially the work of students and lecturers in the creative media field is still not maximized. This can be seen from the rampant piracy of works in the music, information technology, publishing, film, and animation industries. In addition, there are still other problems such as plagiarism of written works, and licensing, especially for the music, photography, and information technology industries. Therefore, it is necessary to have a regulation related to the protection of the works of lecturers and students. The author uses the Normative Juridical research method. The results of the study indicate that the era of instant gratification that was born from technological advances can also have positive and negative impacts, and the protection of the works of lecturers and students who have not been commercialized and are still in the form of drafts that need to be developed further (not yet real) is still not maximized.